Predictors for coronary artery dilatation in Kawasaki disease - Najib Advani; Anisa Rahmadhany; Sarah Rafika (Paediatrica Indonesiana, 2018)
Background Kawasaki disease (KD) is an acute, self-limited, febrile illness of unknown cause that predominantly affects children below 5 years of age. It has a high incidence of coronary complications such as aneurysms. The current treatment of choice is intravenous immunoglobulin, which is costly, with aspirin. Identifying the predictive factors for coronary artery dilatation or aneurysm is important in order to establish the indications for giving immunoglobulin, especially when resources are limited. Objective To identify the predictors for the development of coronary artery dilatation in patients with Kawasaki disease Methods This cross-sectional study was done between January 2003 and July 2013. Inclusion criteria were patients who fulfilled the American Heart Association criteria for acute Kawasaki disease, and had complete clinical, echocardiogram, and laboratory data [hemoglobin, leukocyte, platelet, albumin, C-reactive protein (CRP), and erythrocyte sedimentation rate (ESR)]. All of them received immunoglobulin and aspirin. Results Of 667 KD patients, 275 met the inclusion criteria. There were 185 (67%) males. Subjects’ ages varied between 1 to 157 months. The frequency of coronary artery dilatation at the acute phase was 33.3%. Multivariate analysis showed that >7-day duration of fever and hypoalbuminemia were significant predictive factors for coronary artery dilatation. Conclusion Predictive factors for coronary artery dilatation are duration of fever over 7 days and hypoalbuminemia, while age, gender, hemoglobin level, leukocyte count, and platelet count are not. Frequency of coronary artery dilatation at the acute phase is 33.3%.